An Empirical Test of CAPM: Evidence from Shanghai Stock Exchange 2001-2005 - Wu, Xinxin (2006)
As a financial theory, the Capital Asset Pricing Model (CAPM) has dominated the academic literature and influenced greatly the field of finance and business in practice over four decades. This dissertation examines the validity of the CAPM in the Shanghai Stock Exchange (SSE) which is one of the two stock exchanges in the mainland China for the period Jan 2001-Dec 2005. Employing the approach proposed by Fama and MacBeth (1973) with modifications suggested by Pettengill et al. (1995), I reach a conclusion that is inconsistent with Fama and MacBeth (1973)'s finding as the unconditional CAPM is not valid in the SSE, while conditional CAPM is inapplicable either since there only exist weak insignificant beta-return relationship. Using beta as the only proxy for risk is questionable. In addition, after comparing the empirical SML with the theoretical SML under the conditional CAPM, the slope of the relationship between realized return and beta is less than that of the relationship between expected return and beta predicted by the CAPM with the SML is steeper positively in up market and flatter negatively in down market. In general, the CAPM does not hold in the Chinese stock market.